Secular Humanism and Islamic Humanism – Is there a Common Ground? - Siti Hadija Mohd (JUSPI (Jurnal Sejarah Peradaban Islam), 2019)
In the modern and post-modern world, we have loosely used the term humanism to describe many subjects and the use has been too broad for its specificity and objectivity to be precisely comprehended. In fact, at many points, it has lost positivity in light of discussion within the current century. The term humanism or humanist came from the 15th-century Italian academic world to describe the process of teaching and learning of art and literature between teachers and students. It is very interesting to find out that both the ancient Greeks-Romans and the early modern European use of the concept of humanism was very much in order to detach from the rising of scientific and empirical processes, as well as the rise of modern knowledge.  Either way, the point attempted to be broken here is the fact that the early history and use of the concept of modernism had completely nothing to do with the detachment of religion or a divine influence from human life and choice. Humanism in both ancient Roman and middle-age European had little or no correlation with trying to steer clear neither from any religious influence nor from trying to be modernized with new knowledge from the scientific world. Humanity and humanism in Islam shall be limited to the recognition of human rights, effort, kindness, generosity, being productive and giving benefits to others in the society, instead of having the limitless and boundless definition, which has become meaningless.Keywords: Secular humanism, Islamic humanism, ideology.